Metodologia para predição da autoextinção de arcos elétricos C.C. série em sistemas fotovoltaicos com conversores de potência - Putzke, Josué Lopes (2024)
This study proposes a methodology to predict the self-extinction of electric arcs occurring in the series circuit between modules and power converters in photovoltaic systems, considering the influence of control strategies of the power converters on the electric arc. The study aimed to evaluate the main concepts of power conditioning employed in photovoltaic converters, ensuring behaviors similar to constant resistance, voltage, current, or power loads. Initially, the voltage-current characteristic of the electric arc is modeled using experimental data from tests using the electrodes described in the IEC 63027 standard. Then, the methodology is presented, which analyzes the intersection between the circuit model and the predictive range of the electric arc to anticipate self-extinction under different voltages, currents, electrode distances, and behaviors of the power converter in photovoltaic systems. The experimental results validate the developed methodology, especially in extreme cases. It is considered that these results can contribute to the improvement of standards regarding protections against series electric arcs, as well as offer new insights into effective control strategies of converters for extinguishing electric arcs, without the need for arc fault detection.